Vampires on the Silent Screen - Jones, David Annwn. author. aut Link
XXVII, 215 p. 20 illus., 8 illus. in color.
Keywords: This book is the first study of the vampires in silent cinema, presenting a detailed academic yet accessible discussion of the films themselves and their sources. For the very first time, The Fire Elemental from the Wharton brothers’ The Mysteries of Myra (1916) is identified as cinema’s original vampire, his appearance initiating a rich and variegated period of film production that is currently missing from studies of horror cinema. Exciting and ground-breaking, Vampires on the Silent Screen also discusses Drakula Halála / Dracula’s death (1920), the first ever filmic female vampire in Erich Kober’s Lilith and Ly (1919), and the Dracula lookalike, Count Merlin in Alexander Korda’s Magic (1917) as well as many other productions. A socio-cultural framework with critical highlighting of eco-horror theory is used throughout to draw these unique discoveries together. This project is a must read for any horror enthusiasts out there. David Annwn Jones is author of Gothic Machine (2011), Sexuality and the Gothic Magic Lantern (2014), Gothic Effigy (2018), Re-Envisaging the First Age of Cinematic Horror (2018) and ‘Green Trends in Euro-Horror Films of the 1960s and 1970s’ in The Palgrave Handbook of Contemporary Gothic (2020) ‘The Art of Ghostly Projections’ (2021) in The Palgrave Handbook of Gothic Origins and ‘Cinematic Darkness’, in The Palgrave Handbook of Steam Age Gothic (2021).